Pharmaceutical Processing and Quality Control of Bhasma with Special Reference to AbhrakBhasma - Pathak, Richa (International Journal of Pharmaceutical & Biological Archive, 2015)
Pharmaceutical Processing and Quality Control of Bhasma with Special Reference to AbhrakBhasma